PENGARUH MOTIVASI, KEPEMIMPINAN, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI LAZISNU JAWA TENGAH - Romadhon, Muhamad Shahrul; Imron, Muchammad (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research is to determine the influence of motivation, leadership and work discipline on the performance of LAZISNU (Institute Amil Zakat Infaq and Sadaqah Nahdlatul Ulama) employees in Central Java. The population in this study were all central and branch LAZISNU employees throughout Central Java with a total of 158 employees. Furthermore, the sampling technique used was a random sampling technique using the Slovin formula, so that a sample size of 61 respondents was obtained. The required primary data is collected by means of a survey via a questionnaire. The results of data collection were then analyzed using the multiple linear regression analysis method with the help of SPSS Version 22. The results of the research showed that motivation, leadership and work discipline had a significant positive effect on the performance of LAZISNU Central Java employees.